2016
DOI: 10.21010/ajtcam.v13i4.24
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Lycopene Against the Growth of Human Gastric Cancer Cells

Abstract: Background The aim of this study was to investigate the anti-proliferative effect of Lycopene on HGC-27 cells.Materials and methods HGC-27 cells were treated with varying concentration lycopene for 24, 48, 72 h. The cell growth inhibition was analyzed by MTT. Western blotting was used to indicate changes in the levels of LC3-I, LC3-II, ERK (extracellular signal-regulated protein kinase) and phosphorylation-ERK (p-ERK).Results Lycopene displayed antiproliferative activity in HGC-27 cell lines. Western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Therefore they can act as inactivators of radical molecules or as chain‐breaking factors . Studies have shown that lycopene displays antioxidant activities, represses cell multiplication and inhibits the growth of cancer cells . Various factors may account for the quantitative variation of pigments in different Rosa fruits; exposure to sunlight is one of the most important factors in increasing the synthesis of carotenoids .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore they can act as inactivators of radical molecules or as chain‐breaking factors . Studies have shown that lycopene displays antioxidant activities, represses cell multiplication and inhibits the growth of cancer cells . Various factors may account for the quantitative variation of pigments in different Rosa fruits; exposure to sunlight is one of the most important factors in increasing the synthesis of carotenoids .…”
Section: Resultsmentioning
confidence: 99%
“…64 Studies have shown that lycopene displays antioxidant activities, represses cell multiplication and inhibits the growth of cancer cells. 65 Various factors may account for the quantitative variation of pigments in different Rosa fruits; exposure to sunlight is one of the most important factors in increasing the synthesis of carotenoids. 66 Andersson et al 51 noted that high temperature and irradiation have negative effects on the accumulation and biosynthesis of carotenoids.…”
Section: Fruit Phenolic Compositionmentioning
confidence: 99%
“…Additionally, it does not result in noticeable damage to the cell membrane, necrosis and regular apoptosis [46,47]. Treatment of HGC-27 cells with lycopene exhibited significant improvement in LC3-I, p-ERK proteins expressions [48].…”
Section: Cardioprotectivementioning
confidence: 98%
“…Reduced nuclear factor-kappa B (NF-κB) expression, serum level of oxidative stress marker malondialdehyde (MDA) Improved nuclear factor erythroid 2 expressions Reduced the expression of signal transducer and activator of transcription 3 (STAT3) Induced the protein inhibitor of activated STAT3 expression [44,45] Induced cell cycle arrest and modified the potential of mitochondrial membrane, DNA fragmentation [46,47] Treatment of HGC-27 cells with lycopene exhibited significant improvement in LC3-I, Phosphorylated Extracellular Signal-Regulated Kinase (p-ERK) proteins expressions [48] Reduced NADPH oxidase (NOX) 4 activity Lowered invasion, migration, and adhesion, NOX activity, matrix metalloproteinase (MMP)-9, MMP-2 activities and NOX4 protein expression [49] Reduced…”
Section: Anticancermentioning
confidence: 99%
“…In human colon cancer cells (HT-29 cells), treatment with lycopene reduced cancerous cell invasion, expression of MMP-7, GSK-3β, ERK 1/2, AP-1, β-catenin, phosphorylation of Akt while increasing E-cadherin stabilization [21]. Lycopene was found to enhance the autophagy ability of gastric cancer cell line (HGC-27 cell lines) as observed by increment in the expression of LC3-1 accompanied by phosphorylation of ERK while decreasing tumor weight in Balb/c nude mice models carrying HGC-27 cells which were being fed with 20, 30 and 60 mg/kg lycopene per day [63].…”
Section: Anti-cancer Activities Of Lycopene 61 Cell Culture Studiesmentioning
confidence: 97%